The models of the quality expert analysis for the decisions made under target programming - Ilyina, E.P. (PROBLEMS IN PROGRAMMING, 2026)
The models for expert evaluation of decisions quality attaching to the program elements and technological processes of target programming are proposed. The adequacy of these models to the demands of both the target programming and the Balanced Score paradigm is shown.Problems in programming 2008; 4: 60-72